2010
DOI: 10.1007/s11103-010-9641-4
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger nuclease-mediated transgene deletion

Abstract: A transgene, flanked by zinc finger nuclease (ZFN) cleavage sites, was deleted from a stably transformed plant by crossing it with a second plant expressing a corresponding ZFN gene. A target construct, containing a GUS reporter gene flanked by ZFN cleavage sites, a GFP reporter gene and a PAT selectable marker gene, was transformed into tobacco. Basta-resistant plants were regenerated and screened for GUS and GFP expression. A second construct, containing a ZFN gene driven by the constitutive CsVMV promoter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 39 publications
1
80
0
1
Order By: Relevance
“…In previous studies, HR-mediated gene-replacement strategies have been the preferred mode of gene replacement in plants (Wright et al, 2005;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013), while NHEJ-mediated repair of ZFN-induced DSBs has been limited to targeted mutagenesis and transgene removal (Lloyd et al, 2005;Morton et al, 2006;Maeder et al, 2008;de Pater et al, 2009;Tovkach et al, 2009;Osakabe et al, 2010;Petolino et al, 2010;Zhang et al, 2010). Our findings show that the NHEJ DNA-repair pathway can be harnessed for gene replacement in plant species.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In previous studies, HR-mediated gene-replacement strategies have been the preferred mode of gene replacement in plants (Wright et al, 2005;Shukla et al, 2009;Townsend et al, 2009;de Pater et al, 2013), while NHEJ-mediated repair of ZFN-induced DSBs has been limited to targeted mutagenesis and transgene removal (Lloyd et al, 2005;Morton et al, 2006;Maeder et al, 2008;de Pater et al, 2009;Tovkach et al, 2009;Osakabe et al, 2010;Petolino et al, 2010;Zhang et al, 2010). Our findings show that the NHEJ DNA-repair pathway can be harnessed for gene replacement in plant species.…”
Section: Discussionmentioning
confidence: 69%
“…Transgene deletion by ZFNs was recently reported by Petolino et al (2010), who flanked a transgene with the ZFN CCR5 (Perez et al, 2008). In their report, Petolino et al (2010) used a transgenic strategy in which transgenic target plants were crossed with CCR5 ZFNoverexpressing plants, giving rise to targeted offspring. Here, we expand the use of transgene delivery to the important model plant Arabidopsis with an efficiency of 28% (calculated for actual deletion events; Table I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious application of such an approach is the use of artificially constructed modular endonucleases, such as meganucleases (26), zinc finger nucleases (27), or transcription activator-like effector nucleases (28), that are designed to cut at a specific site in the gene of interest. Recent studies demonstrated that the aforementioned nucleases can be applied in the same way as I-SceI used in our study for different DSB-induced recombination reactions in plants (8,15,19,29). For commercial application, the donor vector might contain a GT cassette flanked by two recognition sites of a site-specific endonuclease that would also cut within the target locus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…removal, replacement, and addition of expression cassettes by NHEJ) can potentially be achieved by transient ZFN expression in target cells, with or without the addition of a donor DNA molecule (Weinthal et al, 2010). Indeed, both I-SceI-and I-CeuI-mediated transgene addition (Salomon and Puchta, 1998;Chilton and Que, 2003;Tzfira et al, 2003) and ZFN-mediated transgene deletion (Petolino et al, 2010) have been reported in plant cells. In addition, we have recently demonstrated that ZFN-and NHEJ-mediated gene replacement is also feasible in plant species (D. Weinthal, T. Taylor, and T. Tzfira, unpublished data).…”
Section: Discussionmentioning
confidence: 99%